Computer vision based automated mango grading – a review - Supekar, Amruta; Wakode, Madhuri (Journal of Postharvest Technology, 2024)
Mango (Mangifera indica L.) is one of the most famous fruits and is in great demand worldwide. During exports and local mango marketing, quality assessment of mangoes is crucial. It is achieved by a post-harvest process of mango grading. Quality evaluation based on appearance features like ripeness, size, shape and defect, directly affect customer satisfaction and thereby vendor’s economic gains. Such appearance based grading is usually done by humans just by inspection with naked eye. However manual sorting could be inconsistent, inaccurate, time-consuming and labor intensive. Computer vision based mango grading, will lead to consistent, accurate and reliable sorting. In recent years many researchers have made an attempt to perform mango classification/grading using image processing and machine learning techniques. A detailed study of such works, performing mango classification based on grading parameters is done and a precise summary is presented here.